2014
DOI: 10.1038/ncomms5993
|View full text |Cite|
|
Sign up to set email alerts
|

The tumour suppressor LKB1 regulates myelination through mitochondrial metabolism

Abstract: A prerequisite to myelination of peripheral axons by Schwann cells (SCs) is SC differentiation, and recent evidence indicates that reprogramming from a glycolytic to oxidative metabolism occurs during cellular differentiation. Whether this reprogramming is essential for SC differentiation, and the genes that regulate this critical metabolic transition are unknown. Here we show that the tumour suppressor Lkb1 is essential for this metabolic transition and myelination of peripheral axons. Hypomyelination in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 59 publications
8
80
1
Order By: Relevance
“…1D), reflecting the successful and specific excision of OGT in SCs. Although OGT is reported to be critical for cell viability and proliferation in many tissues and cell types (Shafi et al, 2000;O'Donnell et al, 2004), we observed no death or altered proliferation in SCs lacking OGT (data not shown).…”
Section: Ogt Deficiency Causes Abnormal Glucose Metabolism In Schwannmentioning
confidence: 63%
See 3 more Smart Citations
“…1D), reflecting the successful and specific excision of OGT in SCs. Although OGT is reported to be critical for cell viability and proliferation in many tissues and cell types (Shafi et al, 2000;O'Donnell et al, 2004), we observed no death or altered proliferation in SCs lacking OGT (data not shown).…”
Section: Ogt Deficiency Causes Abnormal Glucose Metabolism In Schwannmentioning
confidence: 63%
“…All animal experiments were performed in compliance with institutional animal protocols. OGT-SCKO mice (P 0 -Cre Ϫ/ϩ , OGT loxP/loxP ) and control (Ctrl) littermates (P 0 -Cre Ϫ/Ϫ , OGT loxP/loxP ) were generated by crossing OGT loxP/loxP mice (O'Donnell et al, 2004) to P 0 -Cre mice (Feltri et al, 1999). In all experiments, mice of either sex were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LKB1 is a serine/threonine protein kinase that is expressed in almost all human tissues. LKB1 is a tumor suppressor gene closely related to the occurrence of many kinds of tumors 23 . The activation of LKB1 requires the binding of MO25 and STRAD to the complex 24 .…”
Section: Discussionmentioning
confidence: 99%